Persepsi peternak babi terhadap kinerja penyuluh pertanian lapangan (PPL) di Kecamatan Sonder Kabupaten Minahasa - Rintjap, A K; Lenzun, G D; Wantasen, E (Universitas Sam Ratulangi, 2021)
THE PERCEPTION OF PIG FARMERS ON THE PERFORMANCE OF FIELD AGRICULTURAL EXTENDERS IN SONDER DISTRICT, MINAHASA DISTRICT. This study aims to determine the perception of pig breeders on the performance of field agricultural extension officers (PPL) in Sonder District, Minahasa Regency. This research was conducted using survey methods, direct observation and interviews using a questionnaire. The sample was determined by purposive sampling with the criteria that the largest number of pig breeders received counseling from field agricultural extension workers (PPL). Types of data are primary data and secondary data and use the Slovin formula and Likert scale. Farmers 'perceptions of extension workers' performance were reviewed from the aspect of service quality is agree, from the aspect of responsiveness is not the same, and from the aspect responsibility is doubtful.